SYNTHESIS OF ISLAMIC VALUES AND MODERN MANAGEMENT APPROACHES IN THE MANAGEMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS - Devi Fatwanti; Yosie Kristin Pandriyani; Hodiqotul Atfaliyah; Mulyadi, Rasad (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
The management of Islamic educational institutions faces the challenge of the lack of optimal integration of Islamic values and modern management approaches in institutional management practices. Modern management approaches tend to be applied in a technocratic manner, while Islamic values are often positioned as normative aspects that do not yet function operationally. This study aims to analyze and synthesize Islamic values with modern management approaches in the management of Islamic educational institutions. This study uses a library research approach with data sources in the form of books and scientific journal articles published in 2019 and above that are relevant to Islamic education management, Islamic values in organizations, and modern management theory. The data were analyzed using content analysis and comparative analysis techniques to find conceptual commonalities and opportunities for integration between the two approaches. The results show that Islamic values such as trustworthiness (amanah), justice ('adl), deliberation (sh?r?), responsibility, and ihsan are substantively compatible with modern management principles oriented towards ethical, humanistic leadership and organizational sustainability. The synthesis of Islamic values and modern management approaches has the potential to give birth to a professional, adaptive, and valuable Islamic education management paradigm, as well as to strengthen the institutional effectiveness and Islamic identity of Islamic educational institutions in the global era.